Życie codzienne mieszkańców Bydgoszczy w trakcie pierwszej wojny światowej (1914-1918) w świetle „Dziennika Bydgoskiego” (Kronika Bydgoska, 2018)
The article describes the daily life of the residents of Bydgoszcz during World War I as featured by the daily "Dziennik Bydgoski". Some of the topics depicted include rationing, provisioning in the city, rising prices and crimes. In addition, the author also presented cultural activities, Polish-German relations, work of the Polish societies, and charitable fundraising. This period can be described by growing social discontent and abandoning of the loyal attitude toward the German state by the Polish community in Bydgoszcz. In the conclusion, our attention is focused on deterioration in quality of life among the residents of Bydgoszcz during the described period.